2015
DOI: 10.1126/scitranslmed.aab1216
|View full text |Cite
|
Sign up to set email alerts
|

IgH sequences in common variable immune deficiency reveal altered B cell development and selection

Abstract: Common variable immune deficiency (CVID) is the most common symptomatic primary immune deficiency, affecting ∼1 in 25,000 persons. These patients suffer from impaired antibody responses, autoimmunity, and susceptibility to lymphoid cancers. To explore the cellular basis for these clinical phenotypes, we conducted high-throughput DNA sequencing of immunoglobulin heavy chain gene rearrangements from 93 CVID patients and 105 control subjects and sorted naïve and memory B cells from 13 of the CVID patients and 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 72 publications
3
77
0
Order By: Relevance
“…Such out-of-frame sequences in healthy subjects usually have longer CDRH3 regions than the productive, but unmutated antibody gene rearrangements seen in naïve B cells in the peripheral blood. This length difference indicates that there is a selection against B cells with long CDR-H3 sequences after precursor B-cell development in the bone marrow, consistent with earlier data from Sanger sequencing analysis of antibody genes in human early precursor B cells, and increased self-reactivity of the antibodies encoded by such B cells [18,19]. A second step of selection against antibodies with long CDR-H3 regions appears to occur during the process of somatic mutation and selection that gives rise to affinity maturation, since the CDR-H3s in mutated antibody genes from memory B cells are even shorter than those found in naïve B cells [19,20].…”
Section: Human Antibody Repertoiressupporting
confidence: 86%
“…Such out-of-frame sequences in healthy subjects usually have longer CDRH3 regions than the productive, but unmutated antibody gene rearrangements seen in naïve B cells in the peripheral blood. This length difference indicates that there is a selection against B cells with long CDR-H3 sequences after precursor B-cell development in the bone marrow, consistent with earlier data from Sanger sequencing analysis of antibody genes in human early precursor B cells, and increased self-reactivity of the antibodies encoded by such B cells [18,19]. A second step of selection against antibodies with long CDR-H3 regions appears to occur during the process of somatic mutation and selection that gives rise to affinity maturation, since the CDR-H3s in mutated antibody genes from memory B cells are even shorter than those found in naïve B cells [19,20].…”
Section: Human Antibody Repertoiressupporting
confidence: 86%
“…In addition, decreased diversity of the naive CD27‐B‐cell pool and also decreased somatic hypermutation in CD27 + cells were observed. Since patients also demonstrated clonal expansion of unmutated B cells (preselection), the authors provided new evidence that the B‐cell defects in CVID originated in the pro‐B stage of development in the bone marrow …”
Section: Immunologic Abnormalitiesmentioning
confidence: 99%
“…Since patients also demonstrated clonal expansion of unmutated B cells (preselection), the authors provided new evidence that the Bcell defects in CVID originated in the pro-B stage of development in the bone marrow. 81…”
Section: B-cell Immunitymentioning
confidence: 99%
“…Based on these observations, the authors concluded that there were no qualitative defects in the naive repertoire of the studied CVID patients. In a recent large study, Roskin et al 34 explored BCR repertoire properties in CVID by conducting high-throughput sequencing of BCR rearrangements in total B-cells and in naive and memory B-cells. Of importance, this study included 93 patients and 105 controls which gave significant power to see differences in repertoire characteristics.…”
Section: Predominantly Antibody Disordersmentioning
confidence: 99%